2006
DOI: 10.1063/1.2337543
|View full text |Cite
|
Sign up to set email alerts
|

In situ chemical and structural investigations of the oxidation of Ge(001) substrates by atomic oxygen

Abstract: The exposure of Ge(001) substrates to atomic oxygen was studied in situ to establish the stability of the germanium oxide. After preparing chemically clean and atomically flat Ge(001) surfaces, the Ge samples were exposed to atomic oxygen in a wide temperature range from room temperature to 400°C. The chemical composition of the so-formed oxides was studied by means of x-ray photoelectron spectroscopy, while the structure was observed by reflection high energy electron diffraction. At low substrate temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
81
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(85 citation statements)
references
References 13 publications
3
81
1
Order By: Relevance
“…The same approach in Ge is not effective due to GeO desorption at the surface, which leads to unstable Ge oxide. 120,121 Still, if Ge oxidation is forced far away from the surface, some Is injection can be obtained. Actually, very recently, it was shown that O implantation in Ge followed by 650 C annealing induces the formation of embedded GeO 2 nanoclusters (5-10 nm in size) able to induce a large TED of B.…”
Section: Point Defect Engineering and Enhanced B Diffusionmentioning
confidence: 99%
“…The same approach in Ge is not effective due to GeO desorption at the surface, which leads to unstable Ge oxide. 120,121 Still, if Ge oxidation is forced far away from the surface, some Is injection can be obtained. Actually, very recently, it was shown that O implantation in Ge followed by 650 C annealing induces the formation of embedded GeO 2 nanoclusters (5-10 nm in size) able to induce a large TED of B.…”
Section: Point Defect Engineering and Enhanced B Diffusionmentioning
confidence: 99%
“…9,10 A broad range of solutions was considered, e.g. Ge controlled oxidation 6,11 and deposition of passivating interfacial layer ͑IL͒. 12 Recently, a study on ZrO 2 / GeO 2 stacks prepared by atomic oxygen-assisted MBD ͑Ref.…”
mentioning
confidence: 99%
“…Several studies have described the oxidation conditions for formation of the various Ge suboxide states. 23,24 These results suggest that when Ge NWs are exposed to air, the native oxide of Ge will form the Ge 2 O 3 (Ge 3þ ) stoichiometry predominantly. This oxide state will leave the germanium surface with some dangling bonds that can trap carriers and promote their non-radiative recombination.…”
mentioning
confidence: 91%
“…This oxide state will leave the germanium surface with some dangling bonds that can trap carriers and promote their non-radiative recombination. Annealing of Ge in molecular oxygen is expected to promote the formation of an oxide with the Ge 4þ oxidation state (identified by a chemical shift De ¼ 3.5 6 0.1 eV with respect to the bulk contribution of the Ge 3d levels 24,40 ). If this oxidation reaction occurs primarily at the GeO x /Ge interface, rather than at the oxide surface, a reduced interface trap density should result, [19][20][21] leading to more radiative recombination of photoexcited carriers and stronger bandedge photoluminescence.…”
mentioning
confidence: 99%
See 1 more Smart Citation